The 90 % solution : - Rogers, David (John Wiley & Sons, 2006)
The 90% Solution is about understanding the most important factors impacting today’s stock market, how they influence performance—and how they can be used to produce higher returns. In it, author David Rogers challenges traditional investment strategies, then points the way to new and alternative investment methods that can help you rise above the “expectations for mediocrity” that seem to dominate conventional investment thinking